2011
DOI: 10.1016/j.jfms.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute Spinal Cord Injury in the Cat: Causes, Treatment and Prognosis

Abstract: While any cat may potentially be affected by SCI, there is a tendency for exogenous SCI to be more common in younger individuals and, in the authors' experience, pure-breed cats are very rarely presented. Endogenous SCI can be seen in any breed and is typically a condition of adult cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 46 publications
(72 reference statements)
0
27
0
Order By: Relevance
“…These accompanying injuries may pose more immediate threats to their lives than the damage to the spinal cord. So when evaluating an animal with a neurologic deficit due to a suspected trauma, it is necessary to assess the overall stability of the organism, i. e. function of pulmonary and cardiovascular systems in the first place, then proceed with careful examination of the entire nervous system [9,12,14,45]. The clinical experience has shown that traumatic brain lesions, especially in their mild forms, accompany different traumatic events quite often, and multilevel cord damage is also possible [53,67].…”
Section: Diagnosticsmentioning
confidence: 99%
See 3 more Smart Citations
“…These accompanying injuries may pose more immediate threats to their lives than the damage to the spinal cord. So when evaluating an animal with a neurologic deficit due to a suspected trauma, it is necessary to assess the overall stability of the organism, i. e. function of pulmonary and cardiovascular systems in the first place, then proceed with careful examination of the entire nervous system [9,12,14,45]. The clinical experience has shown that traumatic brain lesions, especially in their mild forms, accompany different traumatic events quite often, and multilevel cord damage is also possible [53,67].…”
Section: Diagnosticsmentioning
confidence: 99%
“…The basic ABC examination (the patency of the airways, the ability of the dog to breathe, and the effectiveness of circulation) is recommended [9,14,31,67]. Most animals with significant traumatic events will present a state of hypovolemic shock due to inappropriate vasodilation, blood loss, or both.…”
Section: Spinal Trauma Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Smaller dogs may be splinted along the ventral cervical region, whereas larger dogs often need dorsal and ventral, or even circumferential splinting. 20 Pain control for animals with spinal cord injury often requires pure opioid agonists (fentanyl, hydromorphone, oxymorphone, or morphine) or a partial opioid agonist (buprenorphine). Splinting the thoracic or lumbar vertebral column is more challenging because of the anatomic location.…”
Section: Spinal Cord Segments C6-t2mentioning
confidence: 99%